Guru yang Peduli: Kepribadian Guru Membentuk Karakter Siswa - Ananda Tazkia Ramadhani; Putri Diana; Ade Irma (Politeknik Kampar, 2025)
This article discusses the personality of caring teachers and their role in shaping student character in schools. Based on interviews with experienced teachers, this article identifies that caring teacher personalities play an important role in shaping positive student character. Caring teachers can increase student motivation, develop self-confidence, and shape positive attitudes. This article also discusses the importance of empathy, patience, and understanding student needs in shaping student character. The results of this study show that caring teacher personalities are essential in shaping students with noble character and achievement. Thus, this article can serve as a reference for teachers and education practitioners to understand the importance of caring teacher personalities in shaping student character.